SMART-SPECIALIZATION OF REGIONAL DEVELOPMENT AS AN IMPORTANT DIRECTION OF IMPROVEMENT ITS COMPETITIVENESS AND INNOVATIVE ACTIVITY - Yatsiuk, O. S. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The research is devoted to the economic essence disclosure of smart specialization in the regional development and the identification of impact directions of such specialization on regional competitiveness and innovation activity. It is determined that smart specialization concept involves the relationship between science, education and economy, and in the context of regional development we are talking about the triad "business – science – public sphere". In accordance with these relations, the smart specialization goal is the optimal use of individual regions and countries potential through the maximum adaptation of possible development directions of science and education in these regions or countries to their specific socio-economic conditions. It has been established that the main advantage of smart specialization at the regional level is to increase its competitiveness and innovation activity, because availability of innovations in modern globalized world is a major economic growth factor. It has been determined the necessity of smart specialization concept implementation in Ukraine in regional policy field, primarily in the direction of attracting universities, other educational institutions and research centers to the determination of regions comparative advantages and to the formulation of strategies for their development based on specialization on such advantages realization.